Monitoring of PCBs in Transformer Oils in Indonesia and Policy Implications for Hazardous Waste Management - Handayani, Lidia; L Febrina; M. Alif (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Polychlorinated biphenyls (PCBs) are toxic, persistent organic pollutants (POPs) that have been historically used in electrical equipment, such as transformers. Despite global bans, residual PCBs remain a concern due to legacy equipment found in developing countries. This study proposes to evaluate the presence of PCBs in six transformer oil samples. Samples of PCBs in six transformer oils were collected from transformers operated by Indonesia’s state-owned electricity company (PLN). The analysis was conducted using Gas Chromatography–Electron Capture Detection (GC-ECD) following US EPA Method 8082A. The results confirm that Aroclor 1254 is the predominant PCB congener, with concentrations varying from non-detectable levels to 20.35 ppm. According to Government Regulation No. 101/2014, two samples fall within the